Mesin Pengolah Sampah Organik Dalam Rangka Memberikan Alternatif Solusi Pengolahan Sampah Daun di Desa Lalang Kecamatan Manggar Kabupaten Belitung Timur - Firlya Rosa (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2014)
The making of organic waste processing machines, especially organic waste from plants in Lalang Village, Manggar District, East Belitung Regency is one of the objectives of the Kuliah Kerja Nyata (KKN) thematic of Universitas Bangka Belitung students. The utilization of organic waste to make compost is an alternative solution to the problem of overcoming landfilling and burning of waste which causes global warming. The design and manufacture of organic waste processing machines, brief training on the use of tools, counseling on making compost from the results of the machine process and counseling on machine maintenance are the main activities in this thematic KKN activity. The results of this activity will have an impact on the community to utilize organic waste from their own yard to be used as compost around the environment at low cost through the use of waste that can pollute the environment so as to produce something that is useful and valuable.